Implementation of a paediatric early warning system as a complex health technology intervention. Issue 3 (11th August 2020) - Duncan, Heather; Hudson, Adrienne P
Abstract : The national implementation groups of early warning systems in the UK and Ireland have identified a need to understand implementation, adoption and maintenance of these complex interventions. The literature on how to implement, scale, spread and sustain these systems is sparse. We describe a successful adoption and maintenance over 10 years of a paediatric early warning system as a sociotechnical intervention using the Nonadoption, Abandonment, Challenges to the Scale-Up, Spread, and Sustainability Framework for Health and Care Technologies. The requirement for iterative processes within environment, culture, policy, human action and the wider system context may explain the possible reasons for improved outcomes in small-scale implementation and meta-analyses that are not reported in multicentre randomised control trials of early warning systems.